The Little Old Lady Who was not Afraid of Anything - Williams, Linda 1948-; Lloyd, Megan (New York : Crowell, 1986)
A little old lady who is not afraid of anything must deal with a pumpkin head, a tall black hat, and other spooky objects that follow her through the dark woods trying to scare her.
Accelerated Reader AR